Novel anticorrosive pigments based on waste material for corrosion protection of reinforced concrete steel. (15th November 2015) - Ahmed, N.M.; Mohamed, M.G.; Mabrouk, M.R.; ELShami, A.A.
Highlights: New eco-friendly pigments based on silica fume waste were prepared. Bond strength for rebars coated with paints having the new pigments was not affected. EIS and OCP measurements showed better efficiency for paints with core–shell pigments. Paints having silica fume showed less protection efficiency than core–shell pigments. Core–shell pigments can replace commercial epoxy paints in protecting rebars. Abstract: The performance of concrete specimens containing reinforced rebars coated with films having silica waste and core–shell pigments containing silica as core (80–90%) covered with Zn, Sr, Zn⋅Sr phosphates (10–20%) were compared. Core–shell particles are new trend in anticorrosive pigments comprising core which is cheap material (major) covered with efficient expensive material (minor). The corrosion resistance of rebars was measured using EIS and half cell potential besides measuring the bond strength at the rebar/concrete interface. The results revealed that embedded rebars coated with paints containing the pigments exhibited better efficiency and did not affect the bond strength between rebar and concrete.